The determinants of beef imports in Sweden - Östby Andersson, Felicia (2020)
This paper investigates the determinants of Swedish beef imports using a Vector Autoregression and a Vector Error Correction model. By examining which variables responsible for the volume demanded on imported beef, one can understand how domestic beef production can compete and regain market shares from imported beef. A market relocation has been seen in recent years where country of origin, animal welfare, and environmental issues has been highlighted. Swedish authorities suggest that Swedish beef has an advantage concerning these aspects. The literature records a growing demand for added value at beef production and local beef. Price is crucial when it comes to choices of beef to purchase according to economic theory which somewhat contradicts the literature recordings. Therefore, this paper investigates if added value is of importance when choosing between Swedish or imported beef. The results are comprehended for both the short and long run. The results show that beef import is significantly positively influenced by factors such as Gross National Income export and its price. This corresponds to economic theory in which the demand is dependent on the consumer budget whereas an increase in income, which in this study is measured by Gross National Income, will increase demand for all normal goods. Export and its price are indirect variables for the budget since export increases revenue and thereafter the budget. Local beef has less elasticity than other beef. Therefore, the assumption of Swedish beef having an advantage in the local origin aspects. It is also assumed that Sweden has a less negative effect of added value, which is supported by the findings. Irrespective of the lag length, domestic production, import price, and added value is the variables with negative impact on import in both models. This confirms earlier literature about consumers preferring added value beef with Swedish origin. On the other hand, imported beef has a greater advantage in the lower price for which domestic beef does not have a larger market share. The origin and the higher added value that Swedish beef involves seeming to be the filling between the price gap in between import and domestic beef as the market shares are on a fifty percent level between the two. In the short-run model, the variables had more impact on imported beef. This is interpreted as the importance of the allocation in consumer preference not being recorded long enough for addressing as a trend in the long-run model. Omitted variables can also be influencing a long-run result.